Vascular risk levels affect the predictive value of platelet reactivity for the occurrence of MACE in patients on clopidogrel - Reny, Jean-Luc; Fontana, Pierre; Hochholzer, Willibald; Neumann, Franz Josef; Berg, Jurrién ten; Janssen, Paul W.; Geisler, Tobias; Gawaz, Meinrad; Marcucci, Rossella; Gori, Anna-Maria; Cuisset, Thomas; Alessi, Marie-Christine; Berdagué, Philippe; Gurbel, Paul A.; Yong, Gerald; Angiolillo, Dominick J.; Aradi, Daniel; Beigel, Roy; Campo, Gianluca; Combescure, Christophe (Thrombosis and Haemostasis, 2016)
Prior studies have shown an association between high on-clopidogrel platelet reactivity (PR) and the risk of major adverse cardiovascular events (MACE). However, large intervention trials on PR-tailored treatments have been neutral. The role and usefulness of PR with regard to levels of cardiovascular risk are unclear. We undertook a systematic review and meta-analysis of individual patient data on MACE outcomes (acute coronary syndromes (ACS), ischaemic strokes, and vascular deaths) in relation to PR and its interaction with cardiovascular risk levels. PR was determined using ADP-induced light transmission aggregometry with a primary concentration of 20 μM ADP. Thirteen prospective studies totaled 6,478 clopidogrel-treated patients who experienced 421 MACE (6.5 %) during a median follow-up of 12 months. The strength of the association between the risk of MACE and PR increased significantly (p=0.04) with the number of risk factors present (age> 75 years, ACS at inclusion, diabetes, and hypertension). No association was detected in patients with no risk factor (p=0.48). In patients presenting one risk factor, only high-PR was associated with an increased risk of MACE (HR 3.2, p=0.001). In patients presenting ≥ 2 risk factors, the increase of risk started from medium-PR (medium-PR: HR=2.9, p=0.0004; high-PR: HR=3.7, p=0.0003). PR allowed the reclassification of 44 % of the total population to a different risk level for the outcome of MACE, mostly in intermediate or high risk patients. In conclusion, the magnitude of the association between PR and MACE risk is strongly dependent on the level of cardiovascular risk faced by patients on clopidogrel.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Clopidogrel; drug response; platelets; cardiovascular diseases; ischaemic events